Intimate partner violence among adolescent girls and young women in Bulawayo, Zimbabwe and perceived barriers and facilitators to the provision of psychosocial interventions in salons - Ndondo, Nonhlanhla (Department of Psychiatry and Mental Health, 2025)
Background. Women are disproportionately affected by intimate partner violence (IPV), particularly those in low-to-middle-income countries (LMIC). Recent research data suggests that IPV prevalence among adolescent girls and young women (AGYW) in Zimbabwe is estimated to be 36.5%. Innovative intervention models that leverage gendered spaces to provide IPV support have shown great potential in high income countries, but little is known about these in LMIC settings, including in Zimbabwe. The current qualitative study explored the experiences of IPV among AGYW as well as the feasibility of the use of pre-existing female spaces such as salons to provide psychosocial interventions in Bulawayo, Zimbabwe. Methods. Nine AGYW who had experienced IPV participated in virtual and in-person key informant interviews. Two focus groups were conducted with salon and spa workers to explore the potential use of salon-based interventions (n=10). Purposive sampling was used as a recruitment strategy. Thematic analysis was used to analyse the data. Results. The findings indicated that in this study, AGYW participants' experiences of IPV consisted mainly of physical IPV such as being beaten with an object, being slapped, or punched with a fist, followed by psychological and lastly, sexual IPV. The results of the study highlighted the factors that seemed to predispose AGYW participants to IPV such as sociocultural influences, economic disempowerment and partner characteristics and behaviours. AGYW participants also discussed the negative physical and mental health impact of the psychological and sexual abuses they had encountered. Both salon workers and the AGYW interviewed identified peer support facilitated by the positive social capital created in salons, as well as the female centeredness of salons as conducive elements for an acceptable intervention. However, some speculations around confidentiality and accessibility to salons were some of the potential barriers identified for implementing salon based IPV interventions. Conclusion. The findings of this study indicated that there is a need to identify and address IPV, as well as the mental health consequences that AGYW experience due to IPV. While the use of predominantly female spaces, in this case salons, were discussed as feasible spaces to incorporate into IPV support models for AGYW, there were certain barriers which will need to be addressed for this to be considered. In addition, it was clear that the content of such interventions needed to include not only IPV and associated mental health issues, but also include other components such as economic empowerment of AGYW, while also challenging traditional gender norms through salon-based interventions. Furthermore, AGYW alluded to their preference for IPV psychosocial support interventions to be peer-based and female-driven. Salons typically provide these aspects, hence increasing their viability as a choice for community based IPV support.